Investigation of the susceptibility of Candida auris and Candida albicans to chemical disinfectants using European Standards EN 13624 and EN 16615. Issue 4 (August 2020) - Müller, P.; Tan, C.K.; Ißleib, U.; Paßvogel, L.; Eilts, B.; Steinhauer, K.
Summary: Background: Since the first appearance of Candida auris in 2009, this yeast has become a relevant pathogen in the clinical field. C. auris has been detected on various surfaces in health facilities, and is therefore a target for appropriate disinfection procedures. Preventive measures have to be implemented based on disinfectants with proven efficacy against C. auris . Aim: The chemical tolerance of C. auris was compared with the surrogate test organism Candida albicans as established in the European standards (EN). In this way, conclusions will be drawn as to whether the disinfectants tested according to EN 13624 and EN 16615 are at least equally effective against C. auris. Methods: The chemical susceptibility of C. auris and C. albicans was investigated using standardized EN test protocols. EN 13624 and EN 16615 were used in this study to examine two commercially available surface disinfectants based on alcohol and quaternary ammonium compounds (QACs), respectively. In addition, the survival rates of the two yeast species were studied on a defined test surface simulating practical conditions. Findings: In comparison with C. albicans, C. auris was found to be significantly more susceptible to the alcohol- and QAC-based disinfectants used in this study. C. albicans was found to be more tolerant to drying on the test surface in EN 16615, yielding higher recovery rates. Conclusion: C. albicans is a suitable surrogate test organism when targeting yeasticidal efficacy, which, based on EN 13624 and EN 16615, includes efficacy against the human pathogen C. auris .